ENT 530 Social Media Portfolio: Brownkies / Muhammad Alif Farhan Mahmud - Mahmud, Muhammad Alif Farhan (2021)
Brownkies or as known as brownies cookies were very popular now. This small business starts at one level of management, which is all handled by the same person. This organization uses online like Shopee, WhatsApp and Facebook or Cash on Delivery systems. We also provide customers who live near our area with walk-in services. People who love cookies and bakery are our target market.